Efficacy of Capecitabine Monotherapy as the First-line Treatment of Metastatic HER2-negative Breast Cancer. Issue 4 (July 2015) - Babacan, Taner; Efe, Orhan; Hasirci, Ahmet S.; Demirci, Fatih; Buyukhatipoglu, Hakan; Balakan, Ozan; Sarici, Furkan; Kertmen, Neyran; Esin, Ece; Akin, Serkan; Ates, Ozturk; Aksoy, Sercan; et al.
Aims and Background: Capecitabine is a potent and safe agent that can be used after anthracycline and taxane treatment in patients with metastatic breast cancer (MBC). The purpose of this study was to investigate the efficacy and safety of capecitabine monotherapy as a first-line treatment in human epidermal receptor 2 (HER2)-negative patients with MBC. Methods and Study design: In this single-center trial, a total of 109 HER2-negative patients with MBC who received capecitabine monotherapy as first-line treatment between 2003 and 2014 were retrospectively analyzed. Kaplan-Meier survival analysis was carried out for progression-free survival (PFS) and for overall survival (OS). Two-sided p values of <0.05 were considered statistically significant. Results: Median PFS was 7.0 ± 0.67 (confidence interval (CI) 5.6-8.3) months and median OS was 30 ± 4.1 (CI 21.8-38.1) months. First-line capecitabine treatment for HER2-negative MBC was more effective in the estrogen receptor (ER)-positive patient population compared to the ER-negative group (median PFS 9 vs 4 months (p = 0.002), median OS 33 vs 21 months (p = 0.01)). Indeed, the overall response rate in the ER-negative group was 16%, while this was calculated as 38% for ER-positive cases. While most of our patient population was treated with a higher dose (1250 mg/m 2 ), the observed grade 3-4 toxicities were lower compared to some previously reported phase II and phase III capecitabine studies. Conclusions: Capecitabine monotherapy is an effective and safe regimen for ER-positive, HER2-negative patients with MBC. Its low toxicity profile compared to other intravenous cytotoxic agents and the ease of its oral administration make this agent a preferable option for both physicians and patients.